Design simulation and analysis of deep-sea transducer. (November 2020) - Su, Wei; Yu, Yanting; Zhang, Chao; Sun, Yang; Gong, Jinlong
Abstract: Aiming at the design limitations of current deep-sea transducers, this paper designs and manufactures a deep-sea transducer based on the theoretical analysis of the characteristics of the piezo ring. This transducer is potted and vulcanized into a solid structure with sound-permeable rubber. As a result, not only the deep water pressure resistance is achieved, but also the operating frequency range is broadened by the high-low order coupling vibration between the piezo ring and the sound-permeable rubber. The influences of the main parameters on the electroacoustic characteristics of the transducer are analyzed in detail by FEM. Prototypes are developed subsequently. The measured results show that the simulation and measured results have high consistency. The maximum working depth of the transducer can reach 10000 m, and the beam direction is omnidirectional in the upper hemisphere. In the frequency range of 7∼20 kHz, the transmitter voltage response is higher than 120dB, and the receiver sensitivity is greater than -200dB. This research indicates that the transducer has excellent deep-water characteristic and transmit-receive performance.